Sistem Informasi Pengelolaan Aset Berbasis Web Pada UPT Balai Latihan Kerja Karanganyar - Toni Iksanudin; Hanifah Permatasari; Faulinda Ely Nastiti (Fakultas Ilmu Komputer Universitas Duta Bangsa Surakarta, 2023)
Asset management is one of the important factors in an institution. Therefore, every asset owned must be managed optimally, effectively and efficiently in order to provide decent profits for the institution. UPT Karanganyar Job Training Center is one of the government job training institutions under the auspices of the Department of Trade, Industry and Manpower of Karanganyar Regency. UPT Karanganyar Job Training Center has many assets to support its operations such as computers, air conditioners, vehicles, laboratory equipment and others. Currently, the asset management system at UPT Balai Training Kerja Karanganyar still uses Microsoft Excel. This causes the process of asset maintenance, asset recording and asset reporting at the UPT Karanganyar Work Training Center to be less than optimal, taking longer to track asset data. The purpose of this research is to solve these problems and an information system is needed. This research applies the Waterfall method. The creation of this asset management information system is done using PHP programming language with Codeigniter Framework and MYSQL as the database. Based on tests that have been carried out using black box testing, the system designed can help the problems faced at the UPT Karanganyar Job Training Center.